2022
DOI: 10.3390/jcm11071834
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Intravitreal Anti-Vascular Endothelial Growth Factor Therapies for Managing Neovascular Age-Related Macular Degeneration: A Meta-Analysis

Abstract: Intravitreal injections (IVI) of anti-vascular endothelial growth factor (anti-VEGF) have become the standard of care for age-related macular degeneration (AMD). Although most pivotal trials have used monthly injections, alternative strategies that enable the injections to be administered on a more flexible schedule, including pro re nata (PRN) and treat-and-extend (T&E) regimens, are being applied more frequently. This review sought to provide further scientific evidence about the visual outcomes and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The authors demonstrated a lower mean BCVA gain at 2 years (2.5 vs. 6.74 ETDRS letters here) for less IVT injections (11.4 vs. 14.9 here), but a similar number of consultations (8.9 vs. 8.6 here). Finally, focusing on the most recent meta-analysis by Matonti et al [ 37 ] comparing different IVT anti-VEGF therapies using fixed, PRN, or T&E protocols (a total of 47 different studies), the T&E protocols were found to be the most efficient. Indeed, the T&E protocols showed durable improvements in visual acuity/CRT whilst reducing IVT injection number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated a lower mean BCVA gain at 2 years (2.5 vs. 6.74 ETDRS letters here) for less IVT injections (11.4 vs. 14.9 here), but a similar number of consultations (8.9 vs. 8.6 here). Finally, focusing on the most recent meta-analysis by Matonti et al [ 37 ] comparing different IVT anti-VEGF therapies using fixed, PRN, or T&E protocols (a total of 47 different studies), the T&E protocols were found to be the most efficient. Indeed, the T&E protocols showed durable improvements in visual acuity/CRT whilst reducing IVT injection number.…”
Section: Discussionmentioning
confidence: 99%
“…Note that we took into account findings from the patient group under an irregular treatment protocol for the RAINBOW study [ 24 ]. ALTAIR study [ 18 ]; ANCHOR study [ 3 ]; ARIES study [ 19 ]; ARMADA study [ 36 ]; Kim et al [ 43 ]; MARINA study [ 4 ]; Matonti et al [ 37 ]; Mekjavic et al [ 44 ]; Observe and Plan (O&P) study [ 22 ]; TREX-AMD study [ 11 ]; PrONTO study [ 8 ]; Vardarinos et al [ 45 ]; VIEW study [ 7 ]. BCVA best-corrected visual acuity, ETDRS Early Treatment Diabetic Retinopathy Study, RTE reinforced treat-and-extend …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Rosenberg et al [27] showed that at 1 year of follow-up, improvement of VA was similar between T&E and fixed regimen (p = 0.95) and significantly higher in T&E when compared to PRN regimen (p < 0.0001). In addition, meta-analysis by Matonti et al [28] showed that mean change of BCVA and central retinal thickness was similar between fixed and T&E regimen, which was superior to PRN regimen. The total number of injections needed was significantly lower in T&E regimen compared to fixed regimen (8.2 vs. 10.6; p < 0.0001).…”
Section: Overall Completeness and Quality Of Evidencementioning
confidence: 97%
“…The most common reason for study exclusion were wrong outcome measurement, comparisons, and intervention. The four selected articles for meta-analyses synthesis were consisted of 3 controlled trials [17,28,29] and one retrospective cohort study [11].…”
Section: Search Selectionmentioning
confidence: 99%
“…The use of intravitreal anti-VEGF agents is common in the treatment for neovascular AMD (nAMD) as well as other eye diseases such as polypoidal choroidal vasculopathy, proliferative diabetic retinopathy, and CNV resulting from traumatic choroidal rupture [10,[65][66][67]. Compared to other treatment options for SRH, anti-VEGF monotherapy offers an advantage of being less procedurally complex than surgery, with minimal pain, and a low incidence of complications [20].…”
Section: Intravitreal Anti-vegf Monotherapymentioning
confidence: 99%